PENGGUNAAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN KREATIVITAS SENI RUPA SISWA KELAS VIII.1 SMP NEGERI 30 PADANG - Rika Putri Dewi, Ernis, Ramalis Hakim (Universitas Negeri Padang, 2013)
AbstractThe purpose of this study was (1) to see a picture of the learning process of art using a contextual approach (2) to increase the creativity of art using a contextual approach. The data source of this research is the teacher and the students as the study sample. Data were collected by using observation and interviews. The findings of the study are (1) increased student creativity in the second cycle compared with the first cycle as indicators of creativity by using the contextual approach has been fulfilled (2) an increase in creativity from cycle I to cycle II is 48% (from 24% to 72%) of the students creative.